2011
DOI: 10.1007/s00216-011-5333-4
|View full text |Cite
|
Sign up to set email alerts
|

Biliary excretion of essential trace elements in rats under oxidative stress caused by selenium deficiency

Abstract: The excretion of essential trace elements, namely, Se, Sr, As, Mn, Co, V, Fe, and Zn into the bile of Se-deficient (SeD) Wistar male rats was studied using the multitracer (MT) technique, and instrumental neutron activation analysis (INAA). Normal and Se-control (SeC) rat groups were used as reference groups to compare the effects of Se levels on the behaviors of the essential trace elements. The excretion (% dose) of Se, Sr, As, Mn, Co, and V increased with Se levels in the liver. The biliary excretion of Mn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In contrast to Fe and Zn, the Cu levels in rat liver tissue increased as a result of Se deficiency. Yamasaki et al (2011) observed decreased biliary excretion of Se, As, Mn, Fe, and Zn under Se-deficient conditions compared with that in normal rats and the enhanced biliary excretion of Mn and As in Se-adequate conditions. These observations were related to the element complexation with glutathione (GSH).…”
Section: Resultsmentioning
confidence: 63%
“…In contrast to Fe and Zn, the Cu levels in rat liver tissue increased as a result of Se deficiency. Yamasaki et al (2011) observed decreased biliary excretion of Se, As, Mn, Fe, and Zn under Se-deficient conditions compared with that in normal rats and the enhanced biliary excretion of Mn and As in Se-adequate conditions. These observations were related to the element complexation with glutathione (GSH).…”
Section: Resultsmentioning
confidence: 63%
“…Zn is also present in the structure of SOD enzyme as much as copper is present. The element Zn, which is present in the plasma freely, is the cofactor of SOD enzyme; it binds with biological molecules and prevents Fe and Cu from binding those molecules; hence, it prevents the oxidative damage that may occur (Khaled et al, 1997; Yamasaki et al, 2011). Both Cu and Zn amounts in the kidney and lung tissues and the serum show parallel increase or decrease.…”
Section: Discussionmentioning
confidence: 99%